Usability Analysis using Usefulness, Satisfaction, and Ease-of-Use Questionnaire on the Digital Banking - Carolina Rachel Pirie; Johan J. C. Tambotoh (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
In order to give a seamless transaction, particularly during COVID-19 pandemic, private and public bank institution in Indonesia released digital banking application that is easier to use by smartphone. Nonetheless, there are several complaints from the customer regarding the dissatisfying experience of using digital banking apps. Hence, this research aims to analyze the effect of usability in user experience on customer satisfaction based on 4 variables namely Usefulness, Ease-of-Use, Ease-of-Learning as independent variables, and Satisfaction as a dependent variable on the USE Questionnaire. These variables can be used as references to usability enhancement for digital banking apps to give quality services to customers and be able to compete with competitors. Behavioral Science Research (BSR) is the approach used in this research using the quantitative method. The statistical method used in this research is multiple linear regression analysis. The result of this research shows that 1 out of 4 research hypotheses is rejected (Hypothesis 3) proving that there is no effect of the Ease-of-Learning variable on the Satisfaction variable. However, the value of the t-calculated of Ease-of-Learning variable is 2,478 nearly approach the value of t-table 2,600 showing that this variable is almost capable to give the effect of the Satisfaction variable.